A veterinary virapalooza: a summary of the 2024 American Society for Virology (ASV) Veterinary/Zoonotic Virology Satellite Symposium and online H5N1 panel discussion - Broadbent, Andrew (Journal of virology, 2025)
The year 2024 saw veterinary/zoonotic virology take center stage once more as the American Society for Virology (ASV) hosted a satellite symposium on the subject in June and an online panel discussion in December. The symposium comprised six talks from experts on viruses of economic importance to agriculture and of public health importance. The viruses in question spanned foot and mouth disease virus (FMDV), African swine fever virus (ASFV), Marek's disease virus (MDV), severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and influenza A viruses (IAVs), and topics covered fundamental virology, applied virology, epidemiology, and surveillance. The goal was to emphasize that improving the control of animal viral diseases requires an integrated, holistic approach involving academia, government, and industry labs undertaking research on basic virology, vaccinology, epidemiology, and surveillance. Moreover, the symposium aimed to highlight career opportunities in the agricultural/veterinary sector for those with virology training. Six months following the symposium, the ASV held an online panel discussion on the ongoing H5N1 IAV situation in poultry, cattle, and people to provide more up-to-date information to its membership. A summary of the talks and discussions is presented here.